2017
DOI: 10.3389/fnhum.2017.00354
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Hypothesis about the Etiology of Autism Spectrum Disorders

Abstract: Previous models or hypotheses of autism spectral disorder (ASD) failed to take into full consideration the chronological and causal developmental trajectory, leading to the emergence of diverse phenotypes through a complex interaction between individual etiologies and environmental factors. Those phenotypes include persistent deficits in social communication and social interaction (criteria A in DSM-5), and restricted, repetitive patterns of behavior, interests, or activities (criteria B in DSM-5). In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 178 publications
(198 reference statements)
1
31
0
2
Order By: Relevance
“…ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition. Although the molecular and neural mechanisms underlying ASD remain largely unknown, a previous study suggested that ASD may result from alteration in brain development during early life, such as the excitatory-inhibitory (E-I) imbalance in the autistic brain can affect the sensory, memory and emotional systems 4 , indicating the necessity of early intervention. Without directly monitoring the neuronal E-I balance, current behavioural interventions for ASD at preschool age are mainly behavioural intervention, including parentsmediate Early Start Denver Model and the Applied Behaviour Analysis 5 .…”
Section: Introductionmentioning
confidence: 99%
“…ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition. Although the molecular and neural mechanisms underlying ASD remain largely unknown, a previous study suggested that ASD may result from alteration in brain development during early life, such as the excitatory-inhibitory (E-I) imbalance in the autistic brain can affect the sensory, memory and emotional systems 4 , indicating the necessity of early intervention. Without directly monitoring the neuronal E-I balance, current behavioural interventions for ASD at preschool age are mainly behavioural intervention, including parentsmediate Early Start Denver Model and the Applied Behaviour Analysis 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar timing effects of VPA exposure are also observed in rodents [20,21], with effective treatments likely being associated with processes related to neural tube closure [22]. Hypoplasia of the pons in the brainstem, occurring immediately following neural tube closure, has been proposed as one of the unifying causes of autism phenotype [23]. The VPA rodent model appears to possess face validity and construct validity to model human ASD, as VPAexposed rodents seem to express a similar superficial behavioural phenotype as people with ASD [24].…”
Section: Introductionmentioning
confidence: 81%
“…Historically, the brainstem was at the center of the first brain-based hypothesis of ASD, which theorized that this early-developing neural structure was responsible for the behavioral features of autism ( Rimland, 1964 ). Recently, ASD symptomatology was ascribed to the hypoplasia of the brainstem’s pons, supporting the neurodevelopmental model of autism and the critical role of the brainstem in ASD behaviors ( Inui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 85%
“…These processes lead to an integrative brain where both structure and function of the more complex cortical circuitry rely on the fidelity of the ancestral brain wiring and the efficacy of “lower level” processing. Even a minor disruption of the early neurodevelopmental events could lead to altered brain connectivity and function, affecting integrity of the lower level processing first, and, as a consequence, perturbing the function of the higher order neurocircuitry ( Rodier, 2002 ; Hammock and Levitt, 2006 ; Thompson and Levitt, 2010 ; Inui et al, 2017 ). In all, the brainstem is uniquely positioned to be an initiating link in the unfolding of the hierarchical brain development, suggesting its implication in the whole spectrum of functions that the mammalian brain performs, including the functions traditionally attributed to higher order circuitry.…”
Section: Brainstem Anatomy and Developmentmentioning
confidence: 99%
See 1 more Smart Citation